Transforming Education Through Project-Based Learning (PjBL): Enhancing Students' Learning Outcomes and Critical Thinking - Ayu Wulandari, Medita; Senen, Anwar; Savira Wardani, Duhita; Ruqoyyah, Siti (Jurnal Profesi Pendidikan, 2025)
This study explores the impact of Project-Based Learning (PjBL) on teaching social studies to primary school students, specifically focusing on its influence on critical thinking skills and learning outcomes. The research used a mixed-methods approach and employed proportional stratified sampling to select participants from five accredited public primary schools in Banyumas, Central Java. Quantitative data was collected through pre-tests and post-tests to measure students' performance before and after implementing PjBL. Additionally, qualitative insights were obtained from semi-structured interviews with teachers to understand their experiences and perceptions of PjBL. The findings demonstrate a statistically significant positive correlation between PjBL implementation and improving students' critical thinking skills and academic performance in social studies. Furthermore, teachers reported increased student engagement and a more profound understanding of social studies concepts. This research contributes to the existing knowledge of PjBL by providing empirical evidence of its effectiveness in primary education, particularly within social studies instruction. The findings offer practical strategies for educators who aim to use PjBL to enhance critical thinking and academic achievement among young learners.